Cell Encapsulation: Enhanced In Vivo Vascularization of 3D‐Printed Cell Encapsulation Device Using Platelet‐Rich Plasma and Mesenchymal Stem Cells (Adv. Healthcare Mater. 19/2020). Issue 19 (7th October 2020) - Paez‐Mayorga, Jesus; Capuani, Simone; Farina, Marco; Lotito, Maria Luisa; Niles, Jean A.; Salazar, Hector F.; Rhudy, Jessica; Esnaola, Lucas; Chua, Corrine Ying Xuan; Taraballi, Francesca; Corradetti, Bruna; Shelton, Kathryn A.; et al.
Abstract : In article number 2000670 by Alessandro Grattoni and co‐workers, vascularization of a subcutaneously implantable cell encapsulation platform is enhanced via enrichment with plateletrich plasma (PRP) and mesenchymal stem cells (MSCs) in rats and non‐human primates. Timepoint vascularity assessment demonstrates enrichment with PRP and MSCs increases blood vessel density and maturity inside the encapsulation devices, unveiling an optimal window for cell transplantation. Interspecies reproducibility points toward translatability of the technology.